2015
DOI: 10.1515/biol-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of femoral bone osteoporosis in rats treated with simvastatin or fenofibrate

Abstract: Background: The effects of two lipidlowering drugs, simvastatin and fenofibrate on osteoporosis in the femurs of healthy and ovariectomized female rats were investigated quantitatively by histological images and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
5
6
1
Order By: Relevance
“…Formation of new blood vessels for nutrition of bone was observed suggesting an anabolic process. These results were in accordance with Şipos et al 36 who found that simvastatin reduces the effect of ovariectomy-induced OP, indicated by reduced percentage of intertrabecular cavities. But our results are contrary with the findings of Yao et al, 37 who reported that simvastatin does not prevent or restore ovariectomy-induced bone loss in 3-month-old Sprague-Dawley adult female rats 120 days post ovariectomy.…”
Section: Discussionsupporting
confidence: 93%
“…Formation of new blood vessels for nutrition of bone was observed suggesting an anabolic process. These results were in accordance with Şipos et al 36 who found that simvastatin reduces the effect of ovariectomy-induced OP, indicated by reduced percentage of intertrabecular cavities. But our results are contrary with the findings of Yao et al, 37 who reported that simvastatin does not prevent or restore ovariectomy-induced bone loss in 3-month-old Sprague-Dawley adult female rats 120 days post ovariectomy.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to previous studies, this study observed no significant difference in TbTh between the ovariectomized and control groups. Furthermore, compared with the aforementioned studies that have measured the distal femoral metaphysis and distal femoral epiphysis [ 32 , 37 39 , 44 , 59 63 ], the present study showed smaller differences between the ovariectomized and control groups. This might be attributable to how the distal femoral metaphysis and distal femoral epiphysis have more trabecular structures than the femoral neck does.…”
Section: Discussioncontrasting
confidence: 55%
“…Numerous studies have investigated differences in femoral bone quality and quantity between ovariectomized rats and healthy rats [ 44 , 59 63 ]. Regarding the trabecular bone microarchitecture in the femur, Xiang et al [ 59 ] estimated parameters of the trabecular bone microarchitecture at the distal femoral metaphysis and found significant differences of -73%, -97%, 85%, and -71% in the BV/TV, TbTh, TbSp, and TbN between the ovariectomized and control groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Does and Snyder use the multi-exponential T 2 relaxation distribution on the amphibian Xenopus laevis of which sciatic nerve was crushed [6]. Recently the 1 H NMR relaxometry method combined with inverse Laplace analysis [7,8] was successfully used to assess the ovariectomy induced osteoporosis on Wistar Albino rats [9][10][11][12]. The measured T 2 -distribution on different section of rats femur allowed the calculation of the pores sizes distributions as well as the effects of treatment with simvastatin or fenofibrate.…”
Section: Introductionmentioning
confidence: 99%